GAMBARAN FAKTOR RISIKO KEJADIAN HIPERGLIKEMIA PADA PRALANSIA DI DUSUN REJOSARI, KEMADANG, GUNUNG KIDUL, YOGYAKARTA - Desto Arisandi; Maria Asih Triyanti; Nurlaili Farida Muhajir; Siti Fatimah (Universitas Muhammadiyah Semarang, 2015)
Background: Prevalence rate of diabetes mellitus based on clinical diagnose and symp had already reached out 63.6% in 2007 meanwhile that could be increased into 2.1% in 2013 in Indonesia and also that already happened in D.I Yogyakarta amount of 5.4%. Obesity took a part as one of the most important factor which might be caused diabetes mellitus with prevalence rate of 2.9 higher in overweight groups in Indonesia. Rejosari was the coast area which people took a job as fisherman largely and they inclined to take seafood as their meals which had high fat level. The research objectives were describing risk factors of hyperglycemia in middle age in Rejosari, Kemadang, Tanjung Sari, Gunung Kidul, Yogyakarta. Method: This was a descriptive study in middle age which took 60 people of amount as subjects. This carried on February 2015 in Rejosari, Kemadang, Tanjung Sari, Gunung Kidul, Yogyakarta. Data had been collected which were age, sex, diabetes mellitus history in family, education, smoking behavior, waist size measurement, body mass index (BMI) and blood glucose level. Data was analyzed as descriptive and showed in tables, percentages, and narration. Result: Among the 60 people who as subject, 67% of them got hyperglycemia. Hyperglycemia much happened to ≥ 55 years older age group as 73%, male as 71%, lower education level as 78%, having diabetes mellitus history in family as 63%, smoking behavior as 67%, unnormal waist size as 63% and obesity as 74%. Conclusion: Hyperglycemia much happened to ≥ 55 years older age group, male, lower education level, having diabetes mellitus history in family, smoking behavior, unnormal waist size and obesity.Kata Kunci: middle age, blood glucose, hyperglycemia